Left ventricle ejection fraction estimation by point of care echocardiography in patients admitted in intensive care unit - Rana, Suraj; Shrestha, Bishow Kumar; Pant, Chiranjibi; Adhikari, Shital; Regmi, Sudhir (Journal of Chitwan Medical College, 2020)
Background: Point of care ultrasonography (POCUS) by non-cardiologist is a safe and rapidly evolving diagnostic modality for the assessment of left ventricular ejection fraction (LVEF). This study aims to correlate the eyeball estimation of LVEF (EBEF) with modified Simpson’s method and linear measurement in M-mode parasternal long axis view (PLAX). Methods: A descriptive cross-sectional study was conducted at Chitwan Medical College. POCUS was performed in all ICU patients on the day of admission with optimal image acquisition and LVEF was estimated by three different methods and correlation of results were analyzed. Results: Out of total 52 patients studied, median age was 58.38 ± 17.58 years (range: 24 – 89 years). There were 28 males (53.8%) and 24 females (46.2%) in this study. LVEF measured by eyeballing method and modified Simpson’s method had excellent correlation (Pearson’s correlation coefficient (r) = 0.956, P<0.001). However, there was only a good correlation (r= 0.882, P<0.001) between linear measurement method in M-mode view and Simpson’s method. It was found that eyeballing method underestimates EF as measured by Simpson’s method by an average of 2.33% (95% CI: 1.12 – 3.55%).Similarly, EF measurement by linear method overestimates EF as compared to results observed by Simpson’s method by an average of 6.57% (95% CI: 4.87 – 8.27%). Conclusions: Excellent correlation was observed between EBEF and modified Simpson’s method while linear measurements in M-mode may give incorrect estimation of EF especially in patients with regional wall motion abnormality.